Morphological and phylogenetic characterization of a new Cyphellophora (Chaetothyriales, Cyphellophoraceae) species associated with Tetradium ruticarpum from Guangxi Province, China - Mi, Li-Xue; Song, Hai-Yan; Hyde, Kevin D.; Eungwanichayapant, Prapassorn D.; Mapook, Ausana; Chen, Mu-Sen; Hu, Dian-Ming (Phytotaxa, 2025)
The order Chaetothyriales comprises a diverse group of dematiaceous fungi, including black yeasts and their filamentous relatives, which exhibit remarkable ecological and taxonomic diversity. During a survey of endophytic fungi associated with the medicinal plant Tetradium ruticarpum in Guangxi Province, China, we isolated a new hyphomycetous asexual morph with inconspicuous mononematous conidiophores, short cylindrical phialidic conidiogenous cells bearing small collarettes, and one‐celled guttulate conidia forming slimy masses at the phialide tips. Based on detailed morphological examination and multi-locus phylogenetic analyses of ITS, LSU, and tub2 sequences, we propose the hyphomycetous taxon as a novel species, Cyphellophora guangxiensis. The discovery of this species enriches the diversity of Chaetothyriales in China and provides new insights into the endophytic fungal communities associated with the medicinal plant, T. ruticarpum. A full description, illustrations, and phylogenetic analysis results of the new species are provided.